The Role of Immunocytochemical Markers to Differentiate Primary from Secondary Neoplastic Hepatic Masses: A Diagnostic Challenge on Cytology - Jenna B BHATTACHARYA; Shyam Lata JAIN; Subbarayan DEVI (Türk Patoloji Dergisi, 2021)

(untitled)
Objective: It is challenging and difficult to differentiate primary from metastatic hepatic masses solely on cytology. The present study aimed to correlate cytomorphological spectrum of hepatic masses with immunocytochemical markers to differentiate primary from metastases in liver. Material and Method: The present study comprised of 30 clinico-radiologically suspicious cases of neoplastic hepatic masses. Ultrasound-guided fine needle aspiration smears and cell blocks were prepared as per standard technique; two of the smears were air-dried and Giemsa stained to study cytomorphological features. A panel of markers (HepPar-1, CD 10, CK7, CK19, CD34, and MOC-31) were studied both in smears and cell blocks.